The cardinalfish Fowleria isostigma in the Red Sea and the validity of F. punctulata (Perciformes: Apogonidae) - Gon, Ofer; Bogorodsky, Sergey V. (Zootaxa, 2010)
The Red Sea has five species of the apogonid genus Fowleria, including F. isostigma, a Pacific Ocean species not yet known from the western Indian Ocean proper. Previously, F. isostigma was placed in the synonymy of F. punctulata (Rüppell 1838). However, the taxonomic status of the latter has not been established and in previous works it was placed in the synonymy of F. aurita or F. variegata. This paper compares Red Sea specimens identified as F. isostigma with F. variegata and with the type specimens of F. punctulata. The presence of F. isostigma in the Red Sea is established and F. punctulata is confirmed as a junior synonym of F. variegata. The holotype of F. punctulata is identified by the size given in the original description. A key to the Red Sea species of Fowleria is provided.